Effect of arthropods abundance on the red junglefowl population in oil palm plantation habitat - Arshad, Muhammad Irshad; Hussin, Mohamed Zakaria (Scientific Information Centre, Pakistan Council of Scientific and Industrial Research, 2013)
The study was conducted for one year in the 4-year and 8-year old oil palm plantation at Sungai Sedu Estate, Selangor, Malaysia, to observe whether the abundance of arthropods affects the density of red junglefowl (Callus gallus spadiceus). The arthropods were collected by three methods i.e., litter, pitfall and sweep net. The results indicated that the arthropods abundance in both the study areas was found to be almost similar. It is suggested that arthropods abundance has little effect on the density of red junglefowl in oil palm plantation.